Quantitative analysis of aromatics for synthetic biology using liquid chromatography. Issue 1 (23rd September 2016) - Lai, Bin; Plan, Manuel R.; Averesch, Nils J.H.; Yu, Shiqin; Kracke, Frauke; Lekieffre, Nicolas; Bydder, Sarah; Hodson, Mark P.; Winter, Gal; Krömer, Jens O.
Abstract: The replacement of petrochemical aromatics with bio‐based molecules is a key area of current biotechnology research. To date, a small number of aromatics have been produced by recombinant bacteria in laboratory scale while industrial production still requires further strain development. While each study includes some distinct analytical methodology to quantify certain aromatics, a method that can reliably quantify a great number of aromatic products and relevant pathway intermediates is needed to accelerate strain development. In this study, we developed a robust reverse phase high performance liquid chromatography method to quantify a wide range of aromatic metabolites present in host microorganisms using the shikimate pathway, which is the major metabolic pathway for biosynthesis of aromatics. Twenty‐three metabolites can be quantified precisely with the optimized method using standard HPLC equipment and UV detection, with the mobile phase used for chromatography also compatible with mass spectrometry (MS). The limit of quantification/detection is as low as 10 −10 to 10 −13 mol, respectively, which makes this method feasible for quantification of intracellular metabolites. This method covers most metabolic routes for aromatics biosynthesis, it is inexpensive, robust, simple, precise and sensitive, and has been demonstrated on cell extracts from S. cerevisiae genetically engineered to overproduce aromatics. Abstract : The Shikimate pathway is a key metabolic pathway for the biosynthesis of aromatics, which could be used as industrial fine and bulk chemicals. In this biotech method a simple liquid‐chromatography‐based method to quantify major intermediates and aromatic products of or derived from this pathway in one injection is presented. This work could help to identify metabolic engineering targets and contribute to strain development for aromatic biosynthesis.